Dual‐Solvent Li‐Ion Solvation Enables High‐Performance Li‐Metal Batteries. Issue 25 (9th May 2021) - Wang, Hansen; Yu, Zhiao; Kong, Xian; Huang, William; Zhang, Zewen; Mackanic, David G.; Huang, Xinyi; Qin, Jian; Bao, Zhenan; Cui, Yi
Abstract: Novel electrolyte designs to further enhance the lithium (Li) metal battery cyclability are highly desirable. Here, fluorinated 1, 6‐dimethoxyhexane (FDMH) is designed and synthesized as the solvent molecule to promote electrolyte stability with its prolonged –CF2 – backbone. Meanwhile, 1, 2‐dimethoxyethane is used as a co‐solvent to enable higher ionic conductivity and much reduced interfacial resistance. Combining the dual‐solvent system with 1 m lithium bis(fluorosulfonyl)imide (LiFSI), high Li‐metal Coulombic efficiency (99.5%) and oxidative stability (6 V) are achieved. Using this electrolyte, 20 µ m Li||NMC batteries are able to retain ≈ 80% capacity after 250 cycles and Cu||NMC anode‐free pouch cells last 120 cycles with 75% capacity retention under ≈ 2.1 µ L mAh −1 lean electrolyte conditions. Such high performances are attributed to the anion‐derived solid‐electrolyte interphase, originating from the coordination of Li‐ions to the highly stable FDMH and multiple anions in their solvation environments. This work demonstrates a new electrolyte design strategy that enables high‐performance Li‐metal batteries with multisolvent Li‐ion solvation with rationally optimized molecular structure and ratio. Abstract : A strategy is proposed to optimize the electrolyte formulations for Li‐metal batteries. Li‐ion solvating fluorinated molecules with increasing chain lengths are used as main‐solvents to promote electrolyte stability. 1, 2‐Dimethoxyethane (DME) is used as the co‐solvent to enhance the ionic conductivity. The resulting 1 m LiFSI/6FDMH‐DME electrolyte enables dual‐solvent Li‐ion solvation environments, inorganic‐rich solid‐electrolyte interphases, and long cycling of Li‐metal batteries.